2013
DOI: 10.1182/blood-2012-09-457101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of the MYD88 (L265P) somatic mutation in Waldenström’s macroglobulinemia and related lymphoid neoplasms

Abstract: Key Points Using a sensitive method, the MYD88 (L265P) mutation is detectable in all patients with Waldenström’s macroglobulinemia, therefore representing a hallmark of the disease. MYD88 (L265P) is also found in a substantial proportion of patients with IgM-MGUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
225
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 288 publications
(253 citation statements)
references
References 33 publications
14
225
1
4
Order By: Relevance
“…High frequency of CD79A/CD79B mutation was also identified in PCNSL. Our current finding, that the MYD88 mutation was identified in the CSF of BNS without a BCR CD79-based activating mutation supports the concept that BNS might represent a pathogenetically distinct group of PCNSL (Montesinos-Rongen et al, 2011;Poulain et al, 2013b;Varettoni et al, 2013), and may help in the differential diagnosis as CD19 with K/L restriction is observed in the two diseases.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…High frequency of CD79A/CD79B mutation was also identified in PCNSL. Our current finding, that the MYD88 mutation was identified in the CSF of BNS without a BCR CD79-based activating mutation supports the concept that BNS might represent a pathogenetically distinct group of PCNSL (Montesinos-Rongen et al, 2011;Poulain et al, 2013b;Varettoni et al, 2013), and may help in the differential diagnosis as CD19 with K/L restriction is observed in the two diseases.…”
Section: Discussionsupporting
confidence: 66%
“…In our study, the increased level of detection of MYD88 L265P mutation was shown using high sensitive qPCR (allele-specific oligonucleotide-PCR) as compared to Sanger sequencing when present in a very limited number of cells, as exemplified by the higher level of detection of qPCR in IgM monoclonal gammopathy of undetermined significance, characterized with presence of a B lymphocyte cell clone at a very low level, and in minimal residual disease evaluation (Treon et al, 2012;Jimenez et al, 2013;Varettoni et al, 2013;Xu et al, 2013). High sensitive qPCR might also increase the chance to identify the presence of the MYD88 L265P mutation at a sub-clonal level, particularly in the context of low cellularity in the CSF following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Subsequent studies from multiple institutions have confirmed MYD88 L265P to be present in the majority of lymphoplasmacytic lymphoma/ Waldenstrom's macroglobulinemia, with reported incidence from 67 to 93%. 12,15,21 The mutation has also been found in 44-87% of IgM monoclonal gammopathy of undetermined significance. 12,15,22,23 In contrast, this abnormality has been found much less frequently in other small B-cell neoplasms, including 4-21% of cases diagnosed as splenic marginal zone lymphoma and 1-10% of chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to prior reports showing that MYD88 mutation is associated with higher serum IgM levels in bone-marrow-based lymphoplasmacytic lymphoma and IgM monoclonal gammopathy of undetermined significance. 12,15, 21 Ho et al 27 have also recently described MYD88 mutations to be associated with an IgM protein in nodal lymphomas as well.…”
Section: F Hamadeh Et Almentioning
confidence: 97%
See 1 more Smart Citation